Contribution of education in orthoptics for a better public health to eye care in Europe - Lança, Carla Costa (2017)
Introduction - Orthoptic education varies widely across the world, with countries offering hospital-based training courses whilst others offer bachelor or master level programs within the university sector. Purpose - To provide a description about Orthoptic Education across Europe; to identify the level of competency proficiency (CP) for different curriculum topics in Orthoptics.